ANALISIS PEMAHAMAN KONSEPTUAL TERHADAP MOTIVASI DAN GAYA BELAJAR SISWA BIMBINGAN BELAJAR - Ananda Nasution; Rina Ayu Wardana; Aulia Elvina Paramesti; Rizka Amalia Febriyanti; Maullatul Hajar Sukarno Putri; Firda Husnia; Risma Azizah (FKIP Universitas Samawa, 2023)
The importance of education in human life is as a guide, with education, human life can run regularly, elementary school education is carried out for 6 years as a requirement for continuing further education, implementing education is not far from learning motivation. Motivation is seen as a mental drive that moves and directs human behavior, including learning behavior. Qualitative research is a research that is used in researching natural objects where the researcher acts as a key instrument whose data collection techniques are carried out in a combined manner, data analysis is inductive and the results of qualitative research emphasize meaning rather than generalization. Tutoring seeks to eliminate as far as possible this access to the learning process while at the same time helping students to be able to make adjustments to themselves and to their environment. Tutoring seeks to eliminate as far as possible this access to the learning process while at the same time helping students to be able to make adjustments to themselves and to their environment.